2019
DOI: 10.1590/abd1806-4841.20197661
|View full text |Cite
|
Sign up to set email alerts
|

Do you know this syndrome? Schimmelpenning-Feuerstein-Mims syndrome

Abstract: Nevus sebaceous is the most common type of organoid epidermal nevus, often located on the face, following the Blaschko's lines and with alterations in the ipsilateral central nervous system. Distinct disorders can be distinguished by the type of association with epidermal nevus. Schimmelpenning-Feuerstein-Mims syndrome is a rare multisystem disorder characterized by sebaceous nevus associated with extracutaneous abnormalities affecting the brain, eyes and bones. We report the case of an 8-year-old female patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…We further considered two potential differential diagnoses. One of them is called Schimmelpenning–Feuerstein–Mims syndrome (SFMS), which is a congenital neuroectodermal symptom complex with nevus sebaceous, malformations, and the possibility of developing dysplasia of the eyes, skin, brain, skeleton, and heart [ 30 ]. Furthermore, this syndrome is often combined with hypophosphatemia.…”
Section: Discussionmentioning
confidence: 99%
“…We further considered two potential differential diagnoses. One of them is called Schimmelpenning–Feuerstein–Mims syndrome (SFMS), which is a congenital neuroectodermal symptom complex with nevus sebaceous, malformations, and the possibility of developing dysplasia of the eyes, skin, brain, skeleton, and heart [ 30 ]. Furthermore, this syndrome is often combined with hypophosphatemia.…”
Section: Discussionmentioning
confidence: 99%
“…3,14---16 Subsequently, in 1957, Gustav Schimmelpenning performed the evaluation of a patient with skin lesions and neurological impairment manifestations caused by cranial malformation and, due to the fact that this condition did not correspond to any other previously described clinical picture, Schimmelpenning categorized it as a neurocutaneous phakomatosis. 5,11 In 1962 Feuerstein and Mims reported a case of a linear nevus associated with seizures and intellectual disability symptoms. 5 Since then, the so-called classic triad used for the diagnosis has been created, which consists of neurological impairment, seizures, and intellectual disability, associated with the presence of a nevus sebaceus.…”
Section: Historical Backgroundmentioning
confidence: 99%
“…5,11 In 1962 Feuerstein and Mims reported a case of a linear nevus associated with seizures and intellectual disability symptoms. 5 Since then, the so-called classic triad used for the diagnosis has been created, which consists of neurological impairment, seizures, and intellectual disability, associated with the presence of a nevus sebaceus. 11 However, subsequent studies have shown that the extracutaneous manifestations of the Schimmelpenning-Feuerstein-Mims syndrome are much more diverse.…”
Section: Historical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Schimmelpenning–Feuerstein–Mims (SFM) syndrome, an epidermal nevus syndrome characterized by skin lesions, has an estimated incidence of 1 per 10 000 live births [ 1 ]. Nevus sebaceous, the most common cutaneous lesion, and verrucous nevus, the less frequent lesion, occur in conjunction with several organic and systemic anomalies such as neurological, skeletal, cardiovascular, ophthalmic, and urologic disorders [ 2 4 ]. As part of these, endocrine abnormalities, such as hypophosphatemic vitamin D resistant rickets, syndrome of inappropriate antidiuretic hormone (SIADH), and more rarely central precocious puberty (CPP), are manifested; however, very few cases have been reported so far [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%